Body image perception and attempts to change weight among female medical students at Mangalore - Priya D; Prasanna K; Sucharitha S; Vaz Nafisa (Wolters Kluwer Medknow Publications, 2010)
Background: Assessing body image self-perception has used BMI as an indicator of nutritional status. The visual analogue scale is a highly effective instrument for assessing people′s level of dissatisfaction with their body weight while evaluating the perceptual component of body image. Objective: By knowing body mass index of female medical students, to find out their pattern of body image perception and any attempts done to change their weight. Materials and Methods: All the students residing in MBBS ladies hostel were included in this study and a questionnaire regarding body image perception, diet, physical activity and attempts to change weight was instituted. Their responses were collected, tabulated, analyzed and interpreted. Results: Among 147 study subjects, according to BMI, 25(17%) were undernourished while 111(75.5%) and 11(7.5%) were normally nourished and overweight respectively. 35(23.8%) of the subjects felt they were lean, 95(64.6%) felt they were normal and 17(11.6%) felt they were overweight. Regarding image satisfaction, 98(66.7%) of them were satisfied with their image and out of 49 who were not satisfied 30 (20.4 %) wanted to reduce weight. Skipping meals was practiced by 42 (28.6%) of subjects. Conclusion: About 75.5% of the study group were having normal BMI. Most of them perceived their image correctly regarding to their weight. Most of the underweight and all overweight females were not satisfied. Underweight females preferred to gain weight and overweight females preferred to lose weight.